Digital-Based Archive Management in higher Educational Environment, Universitas Negeri Semarang (Educational Management, 2022)
Along with the dynamics of organizational activity, archive management activities in the office are becoming increasingly dynamic. Many office practitioners have difficulty managing archives because they lack a good understanding of archive management both conventionally and electronically. This research focuses on the management of digital archives at the Faculty of Law, UNNES by analyzing the obstacles to digital archive management. The method used in the study is qualitative to descriptive research. The result of the research is that the archiving system carried out by the Archives Processor of the Faculty of Law has not been optimally carried out because they do not understand digital archives, with the creation of archive manuals/guidelines digital is expected to be an archive processor at the Faculty of Law to easily carry out digital archive management, thus the digital document storage system has a good influence on the performance of archive managers and for archive processors on stored documents. The application of this research is the ease of managing archives by moving, and finding documents implemented effectively and efficiently for not too long.